Enterpreneurial orientation and relational capability: the network advantage to marketing performance in SMEs - Lustono, Lustono; Lusaputra, Fadhil Ghani; Suryani, Ratna (Jurnal Konseling dan Pendidikan, 2025)
The intention of this study is to enhance the prevailing literature and conceptual framework by investigating the consequence of entrepreneurial approach and relational capability related marketing performance through network advantage. The research follows a empirical approach using a survey method. A purposive sampling technique was employed to select 138 samples of Batik MSMEs in Banjarnegera Regency. The data was obtained through a survey. Data analysis techniques were utilised  employing Structural Equation Modelling (SEM) through the SmartPLS program. The findings from this study demonstrate that entrepreneurial orientation and relational capability each partly have a significant and favourable impact on network advantage. Furthermore, entrepreneurial orientation, relational capability, and network advantage each have a partly positive and significant influence on marketing performance.  The influence of entrepreneurial orientation on marketing performance can be mediated by network advantage, whereas relational capability does not exhibit the same mediating effect.